Priapism in Antipsychotic Drug Use: A Rare but Important Side Effect - Igne Sinkeviciute; Rune A. Kroken; Erik Johnsen (Case Reports in Psychiatry)
Priapism is a rare but important side effect of antipsychotic drugs which may evolve into a urological emergency. Most antipsychotic drugs are alpha-1 adrenergic antagonists, which is thought to be the principal mechanism involved in antipsychotic-induced priapism. Other aetiologies exist, however. A case is presented with multiple episodes of priapism during the use of several different antipsychotic drugs. The case is representative of many patients treated with antipsychotic drugs, as there were hyperprolactinemia, and illicit drug use, which are known causes of priapism. Moreover, the patient used combinations of antipsychotic drugs. The case thus illustrates the etiological complexity which could delay a diagnosis of antipsychotic-induced priapism, and the problem of establishing a link between priapism and one particular ingredient of a drug combination. The case presents how a treatment regimen was finally established balancing antipsychotic efficacy to acceptable side effects and offers guidance to physicians regarding how antipsychotic-induced priapism may be resolved.